Studi Pembuatan Klepon dengan Subtitusi Tepung Ubi Jalar Ungu dan Penambahan Tepung Kacang Almond sebagai Alternatif Makanan Selingan Penderita Diabetes Melitus - Farihatul Islamiyah; Ahmad David Royyifi Arifin; Lilia Faridatul Fauziyah (Yayasan Literasi Sains Indonesia, 2024)
Background: Diabetes mellitus is a metabolic disorder that occurs chronically or chronically because the body does not have enough insulin hormone due to disruption in insulin secretion, insulin hormone that does not work properly or both. Diabetes mellitus is characterized by the appearance of typical symptoms, namely polyphagia, polydyscipsia, and polyuria and some experience weight loss. One of the risk factors for diabetes mellitus is unbalanced intake, where high consumption of fat and sugar can cause obesity and is associated with increased blood glucose. Therefore, appropriate snacks or distractions are needed for people with DM. Klepon with the addition of purple sweet potato flour and almonds can be a new innovation and can be used as an alternative snack for people with diabetes mellitus. Purpose: The purpose of this study was to determine the content of macronutrients and the effect of substitution of sweet potato flour andalmond on the acceptability of klepon's organoleptic quality. Method: Aanalysis used in this study consists of statistical analysis k and power analysis Accept or quality organoleptik. Result: The results showed that there was a significant influence on the nutritional value as well as on the color, taste, aroma and texture of almonds substituted sweet potato flour and almonds. The best treatment is found in P1 treatment cookies. Conclusion: The substitution of sweet potato flour and almonds affects the nutritional value and acceptability of color, taste, aroma, and texture of klepon.